Epigenetic Regulation of Heat Stress in Plant Male Reproduction - Malik, Shikha; Zhao, Dazhong (Frontiers in Plant Science, 2022)
In flowering plants, male reproductive development is highly susceptible to heat stress. In this mini review, we summarized different anomalies in tapetum, microspores, and pollen grains during anther development under heat stress. We then discussed how epigenetic control, particularly DNA methylation, is employed to cope with heat stress in male reproduction. Further understanding of epigenetic mechanisms by which plants manage heat stress during male reproduction will provide new genetic engineering and molecular breeding tools for generating heat resistant crops.